CREATIVE THINKING ABILITY OF HIGH SCHOOL STUDENTS IN SOLVING PHYSICS QUESTIONS BASED ON LOCAL WISDOM - Nurlinda Nompo; MA Martawijaya; Mutahharah Hasyim; Mahir Mahir (Lembaga Penelitian Mahasiswa Penalaran UNM, 2024)
This quantitative descriptive study aims to describe high school students' creative thinking abilities in solving physics problems based on local wisdom. The data obtained in this research is quantitative and analyzed using descriptive statistics. The sample in this research consisted of 45 students. Based on the Gregory test, the validity value obtained is 1. Based on the Gregory test requirements, if V_c≥ 0.75 or ≥ 75%, it can be concluded that all items on creative thinking abilities are suitable for use. The reliability test obtained was 0.83 and was declared reliable. The instrument to collect data was an essay test consisting of 12 questions developed by indicators of creative thinking ability, including indicators of fluent thinking, flexible thinking, original thinking, and elaborative thinking. Based on research data, it was found that the ability to think creatively in solving physics problems based on local wisdom was in the low category. Based on the results of interviews show that 42% of students were unable to explain the relationship between physics concepts in the questions given. It can be concluded that the description of high school students' creative thinking abilities in solving physics problems based on local wisdom is in the low category.